Consumers’ Willingness to Pay for Halal Labelled Chicken Meat - Putri, Wilda Rizkilia; Samsudin, Muh; Rianto, Edy; Susilowati, Indah (JDM (Jurnal Dinamika Manajemen), 2017)
This research aims to analyze the level of the society’s awareness of halal-certified chicken meat, and estimates the values of society’s willingness to pay for halal-certified chicken meat. There are 102 female married moslem respondents in Pedurungan sub-district, Semarang, who were selected using accidental sampling. This study uses several independent variables namely in-come, education, age, chicken meat consumption, awareness of the importance of halal-certi-fied products, and number of family members. The dependent variable in this research is value of respondent’s willingness to pay. The results of observations was tested using the regression model of ordinary least square. The results of the analysis showed that 96 out of 102 respond-ents stated that they were willing to pay for certified halal meat at a range of Rp 36,500.00 to Rp 39,000.00 per kilogram. The variables that influenced respondents’ willingness to pay were: income, education, consumption of chicken meat, halal awareness of products, and number of dependent family. Those variables influenced consumer’s willingness to pay positively and significantly. Meanwhile, the variable age affected significantly at a negative direction.